The demographics of global corporate champions - Nicolas Véron (Bruegel, 2008)
This Working Paper presents a novel dataset documenting the demographics of the world's 500 largest companies by market capitalisation, as of 30 September 2007. Assigning a birth date to a large company is not a straightforward exercise and involves a measure of judgment, which possibly explains why data on corporate demographics have not been more widely researched in spite of their potential interest to policymakers. However, our methodology, based on the collection of narrative data which is publicly accessible online, generates robust results, which we hope may help spur increased interest in corporate demographics. (...)
Keywords: 330